The role of probiotics in human microecology - Babich, Ye; Chepurnaya, M (Annals of Mechnikov’s Institute, 2020)
Today the number of violations in dysbiotic microflora of the gastrointestinal tract increases. This is a consequence of many factors: the effect of negative environmental factors, the uncontrolled use of antibiotics, reduced adaptive capacity of the organism, etc. Probiotic preparations are widely used in the clinical practice to solve the problem of dysbiosis. The properties of probiotics, their impact on the human body and mechanisms of actions of probiotics are presented in the review. The modern requirements for probiotic microorganisms and preparations-probiotics are described in the article. Key words: intestinal